The delicate balance between achieving greatness and respecting legends: Lebron James, Kareem Abdul-Jabbar, and the case of breaking records in sports - Samuel, R. D.; Galily, Y. (Asian Journal of Sport and Exercise Psychology, 2024)
LeBron James made NBA history on February 7, 2023, when he surpassed Kareem Abdul-Jabbar's 39-year-old record to become the all-time leading scorer. Abdul-Jabbar responded to James` achievement with grace and explained why he was not intimidated by it. In this article, we review several examples of athletes who accorded with or feuded against their records getting broken by other athletes. We relate such emotional and public responses to achievement motivation theory in sports as well as to athletes` adaptation to retirement. We further discuss social concepts and factors, such as personal rivalries, political collisions, generation differences, and technology. We believe that while actual responses from athletes might be unpredictable, there are several ideas that can be conceived concerning this phenomenon. We conclude by suggesting avenues for exploration in this under-researched area in sports.